In vitro antimicrobial combinatory effect of Cinnamomum cassia essential oil with 8-hydroxyquinoline against Staphylococcus aureus in liquid and vapour phase - Netopilova, M; Houdkova, M; Urbanova, K; Rondevaldova, J; van Damme, P; Kokoska, L (Journal of applied microbiology, 2020)
AIMS: The objective of the study was to evaluate the antimicrobial interactions between two volatile agents, Cinnamomum cassia essential oil (CCEO) and 8-hydroxyquinoline (8-HQ) against Staphylococcus aureus strains in liquid and vapour phases. METHODS AND RESULTS: In vitro antimicrobial effect of CCEO in combination with 8-HQ was evaluated against 12 strains of S. aureus by broth volatilization chequerboard method. Results show additive effects against all S. aureus strains for both phases. In several cases, sums of fractional inhibitory concentration values of our test combinations were lower than 0·6, which can be considered as a strong additive interaction. Moreover, composition of CCEO was analysed by gas chromatography-mass spectrometry analysis. In the CCEO, 26 compounds in total were identified, where (E)-cinnamaldehyde was the predominant compound, followed by cinnamyl acetate, α-copaene, bornyl acetate and caryophyllene. CONCLUSIONS: Results showed additive in vitro growth-inhibitory effect of CCEO and 8-HQ combination against various standard strains and clinical isolates of S. aureus. SIGNIFICANCE AND IMPACT OF THE STUDY: This is the first report on antibacterial effect of 8-HQ and CCEO combination in liquid and vapour phases. Results of the study suggest these agents as potential candidates for development of new anti-staphylococcal applications that can be used in the inhalation therapy against respiratory infections.
Keywords: chemical composition; Anti-Bacterial Agents; oxychinolin; akrolein; Acrolein; fractional inhibitory concentration; antimicrobial interactions; Microbial Sensitivity Tests; Staphylococcus aureus; volatile compound; GC-MS; Oils, Volatile; plynová chromatografie s hmotnostně spektrometrickou detekcí; antibakteriální látky; oleje prchavé; Cinnamomum aromaticum; Oxyquinoline; mikrobiální testy citlivosti; broth volatilization chequerboard method; Gas Chromatography-Mass Spectrometry; skořicovník čínský